Recreational and Conservation Benefits at the Kapar Bird Sanctuary, Selangor, Malaysia - Amiry, Seddigheh Arab (2009)
This study is done to determine willingness to pay (WTP) of recreational resources in Kapar Bird Sanctuary. The relevant values are estimated by utilizing dichotomous choice form of contingent valuation method (CVM). The logit models are used to analyze the data collected using the dichotomous choice survey design. The open-ended question is used to induce respondents to state their true WTP, and the OLS model is employed to determine the WTP values. On one hand ash produces in the process of electricity production may have pollution on environment on the other hand these are chosen by birds as sanctuary. Now should area be preserved as sanctuary or yet to be exploited for short- term profits. Perhaps economic valuation is one way that this area properly expressed in monetary units, but economic valuation of KBS that have no market, no entrance fee to be charge and have intrinsic value may problems arise. For the purpose of this study the population consists of the residents of Kapar town and the visitors to the recreational site, making a total sample size of 440 that was exactly a split. They were asked their WTP for the conservation of KBS as an excitement place for recreation site. As it is customary to do in most CVM studies, positive respondents with respect to sample groups i.e. among the local residents, 208 of them are selected as respondents, the number of visitors in the study amounts to 198. The results of the analyses show that the mean willingness to pay for local residents ranges from RM4.02 to RM43.23, and for visitors it ranges from RM12.06 to RM60.94. The median WTP is found to be less than the mean WTP, the median for local resident ranges from -RM21.24 to RM42.63, while for visitors it ranges from-RM 14.36 to RM41.09. The WTP estimation from the open-ended question is conditional on the dichotomous choice question. Nonetheless, the combinations of open ended and dichotomous choice model results in WTP values which meet the criteria of consistency and construct validity for CVM study. The OLS model is employed to estimate the annual economic benefit because of the difficulties relating to econometric constraints and inconsistencies. With the local total population of 22,819, the aggregated value or benefit of the Kapar Bird Sanctuary ranges from RM0.291 million to RM0.334 million. Using the social discount rate of 5%, the present value of the benefit is equal to RM5.823 million to RM6.672 million for the local community. If the number of visitors is assumed to the total of 1500 per year, the aggregated WTP ranges from RM0.022 million to RM0.028 million; and using the 5% social discount rate, the annual benefit ranges between RM0.447 million to RM0.550 million. Also this study implies that non-use value should be considered in policy making associated with recreational resources. The findings of this study are important in assists policy maker in management and development of recreational sites in Malaysia.